2017
DOI: 10.1177/0276237417693564
|View full text |Cite
|
Sign up to set email alerts
|

How Images Draw the Eye: An Eye-Tracking Study of Composition

Abstract: In his instructional art book, Andrew Loomis provides images and corresponding diagrams that indicate how the composition of the image should guide the viewer's eye. Using these images, we examined whether participants would follow the suggested cues. Participants' eyes were tracked as they viewed the images, allowing us to take measures of where they entered and exited the image, whether they attended to the focal part of the image, and what path they followed between these components. These measures could th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
(34 reference statements)
1
13
1
Order By: Relevance
“…Our study thus provides strong evidence for the traditional assumption in art literature that pictorial composition guides the movement of the eye. We thus contradict the results of Garbutt and Spehar (2014) and Kirtley (2018) who denied such correlations. However, this is not a real contradiction.…”
Section: Discussioncontrasting
confidence: 95%
“…Our study thus provides strong evidence for the traditional assumption in art literature that pictorial composition guides the movement of the eye. We thus contradict the results of Garbutt and Spehar (2014) and Kirtley (2018) who denied such correlations. However, this is not a real contradiction.…”
Section: Discussioncontrasting
confidence: 95%
“…This strengthens prior findings ( 19 ) that composition does influence the scanpath, but does not dictate the scanpath of the viewer. The results are similar to those of Kirtley ( 29 ), confirming that focal points attract and keep attention but that the entry and exit points are largely not used as intended. Furthermore, it confirms that the compositional line guided the eye but did not dictate either order or direction.…”
Section: Discussionsupporting
confidence: 82%
“…Results indicated that focal points were successful in attracting and keeping attention, but the intended entry and exit points were not used. Furthermore, the compositional line was not closely followed and the compositional elements did not exert a significant influence over eye movements (Kirtley, 2018). Interestingly, children rely on bottom-up processing when free-viewing a painting, but revert to top-down processing when they view the painting again after being given background information.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations